Cultivating Resilience in Part-Time Doctoral Students - Murphy, Liam (GILE Journal of Skills Development, 2024)
In an increasingly competitive world, master’s degrees are becoming the new common educational currency, leading to a markable increase in the number of students pursuing Professional Doctorates to stand out, boost their professional standing, and increase their income. The rise of Professional Doctorates is eclipsing the growth of traditional PhDs, and the academic intakes of the future look to be built of part-time professionals, who must also balance additional stressors such as family and personal life and their day-to-day careers. As such, this author recommends academic institutes promote the skills of resilience to help part-time students manage day-to-day stressors and embark on a more successful doctoral journey. This is an opinion-based paper that utilises lessons learned from the author’s own academic journey and the classic underpinning literature on resilience to recommend three sets of skills and mindsets that could help boost part-time doctoral students’ resilience.